Fear Memory Retrieval Is Associated With a Reduction in AMPA Receptor Density at Thalamic to Amygdala Intercalated Cell Synapses - Seewald, Anna; Schönherr, Sabine; Hörtnagl, Heide; Ehrlich, Ingrid; Schmuckermair, Claudia; Ferraguti, Francesco (Frontiers in Synaptic Neuroscience, 2021)
The amygdala plays a crucial role in attaching emotional significance to environmental cues. Its intercalated cell masses (ITC) are tight clusters of GABAergic neurons, which are distributed around the basolateral amygdala complex. Distinct ITC clusters are involved in the acquisition and extinction of conditioned fear responses. Previously, we have shown that fear memory retrieval reduces the AMPA/NMDA ratio at thalamic afferents to ITC neurons within the dorsal medio-paracapsular cluster. Here, we investigate the molecular mechanisms underlying the fear-mediated reduction in the AMPA/NMDA ratio at these synapses and, in particular, whether specific changes in the synaptic density of AMPA receptors underlie the observed change. To this aim, we used a detergent-digested freeze-fracture replica immunolabelling approach that enables to visualize the spatial distribution of intrasynaptic AMPA receptors at high resolution. AMPA receptors were detected using an antibody raised against an epitope common to all AMPA subunits. To visualize thalamic inputs, we virally transduced the posterior thalamic complex with Channelrhodopsin 2-YFP, which is anterogradely transported along axons. Using face-matched replica, we confirmed that the postsynaptic elements were ITC neurons due to their prominent expression of µ-opioid receptors. With this approach, we show that, following auditory fear conditioning in mice, the formation and retrieval of fear memory is linked to a significant reduction in the density of AMPA receptors, particularly at spine synapses formed by inputs of the posterior intralaminar thalamic and medial geniculate nuclei onto identified ITC neurons. Our study is one of the few that has directly linked the regulation of AMPA receptor trafficking to memory processes in identified neuronal networks, by showing that fear-memory induced reduction in AMPA/NMDA ratio at thalamic-ITC synapses is associated with a reduced postsynaptic AMPA receptor density.